Kesenjangan Etika Profesional TIK dan Perangkat Lunak Bajakan: Kajian Literatur Kontekstual Indonesia - Hendrawan Hendrawan; Lukas Setia Udi; Ibnu Gunawan Prayogo; Abdul Abdul; Agus Cahyadi (Lembaga Pengembangan Kinerja Dosen, 2025)
This conceptual-analytical literature review examines the gap between ethics and practice in Indonesian corporate settings regarding unlicensed software. Three patterns stand out. First, license compliance is frequently overshadowed by short term cost and benefit considerations, subjective norms, and delivery pressure at the unit level. Second, professional codes of ethics are weakly embedded in policies, processes, and role accountability, producing uneven decision paths across functions. Third, unlicensed software creates tangible exposure to malware, legal liability, loss of vendor support, and service disruption that accumulate into operational and reputational risk. To close this gap, the review outlines governance instruments tuned to local practice. COBIT 2019 aligns enterprise objectives with control design. ITIL 4, particularly Service Configuration Management (SCM) and Change Enablement, supports pre-deployment checks and traceable configuration baselines so unauthorized installations are blocked at the source. Complementary measures include curated legal substitutions (notably open-source options with clear policy and vulnerability monitoring), periodic audits that reconcile entitlements against installations, documented handling of detected violations, ethics education using Indonesian cases with post-training evaluation, and routine reporting of unit-level compliance metrics to executives. The contribution is a practical blueprint linking ethical principles honesty, respect for intellectual property and due care to concrete controls in ICT functions in Indonesia.